Evaluation of a new methodology to simulate damage and wear of polyethylene hip replacements subjected to edge loading in hip simulator testing. Issue 4 (29th June 2017) - Partridge, Susan; Tipper, Joanne L.; Al‐Hajjar, Mazen; Isaac, Graham H.; Fisher, John; Williams, Sophie
Abstract: Wear and fatigue of polyethylene acetabular cups have been reported to play a role in the failure of total hip replacements. Hip simulator testing under a wide range of clinically relevant loading conditions is important. Edge loading of hip replacements can occur following impingement under extreme activities and can also occur during normal gait, where there is an offset deficiency and/or joint laxity. This study evaluated a hip simulator method that assessed wear and damage in polyethylene acetabular liners that were subjected to edge loading. The liners tested to evaluate the method were a currently manufactured crosslinked polyethylene acetabular liner and an aged conventional polyethylene acetabular liner. The acetabular liners were tested for 5 million standard walking cycles and following this 5 million walking cycles with edge loading. Edge loading conditions represented a separation of the centers of rotation of the femoral head and the acetabular liner during the swing phase, leading to loading of the liner rim on heel strike. Rim damage and cracking was observed in the aged conventional polyethylene liner. Steady‐state wear rates assessed gravimetrically were lower under edge loading compared to standard loading. This study supports previous clinical findings that edge loading may cause rim cracking in liners, where component positioning is suboptimal or where material degradation is present. The simulation method developed has the potential to be used in the future to test the effect of aging and different levels of severity of edge loading on a range of cross‐linked polyethylene materials. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1456–1462, 2018.